Urban Public Perceptions and Usage of the 'Wira-Wiri Suroboyo' Feeder: Insights from the Theory of Planned Behavior - Pamula, Gisela Geraldine; Christy, Hilary; Syahnufi, Chiara Hanifah; Natalia, Johanna; Sampe Tondok, Marselius (UI Scholars Hub, 2025)
Traffic congestion is a major transportation issue in Surabaya, prompting the city government to introduce solutions such as the